Peranan Serangga untuk Mendukung Sistem Pertanian Berkelanjutan - Akbar Radja Vanderi; Arsi Arsi; Mega Utami; Ahmad Bintang; Delly Salsabila Amanda; Aqilla Noor Sakinah; Reja Malini (Seminar Nasional Lahan Suboptimal, 2021)
Vanderi AR, Arsi A, Utami M, Bintang A, Amanda DS, Sakinah AN, Malini R. 2021. The role of insects to support sustainable agriculture systems. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 249-259. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Insects have the highest number of species among other living things. The understanding that insects are plant-disturbing organisms (OPT) has led to the development of synthetic chemical pesticides that are very damaging to the environment. In fact, insects have many roles to support sustainable agricultural systems. This article aimed to study the role of insects in supporting a sustainable agriculture system. This article was compiled from a study of scientific literature. It has been resulted that the review shows the success of a sustainable agricultural system can be done by utilizing the roles of insects. Such as the role of insects as pollinators of the order Hymenoptera, Lepidoptera and Diptera, and also the role of insects as decomposers of the order Hymenoptera. Then, the role of insects as bioindicators of the orders Hemiptera, Coleoptera, Ephemeroptera, Trichoptera, and Odanata. As well as the role of insects as parasitoids of the order Hymenoptera, and the role of insects as predators of the orders Coleoptera, Hemiptera, and Odonata. The conclusion, the insects do not always have a negative impact, because some of the roles of insects can be utilized to support sustainable agricultural systems.